TWEAK/Fn14 signaling in tumors. Issue 6 (June 2017) - Hu, Guanglei; Zeng, Weihui; Xia, Yumin
TWEAK (tumor necrosis factor–related weak inducer of apoptosis), a member of the tumor necrosis factor superfamily, acts on cells by binding to its only receptor named Fn14 (fibroblast growth factor–inducible 14). Their engagement activates a number of intracellular signal transduction cascades and consequently leads to cell death, proliferation, migration, or survival depending on the cellular contexts. Studies have indicated that the expression of TWEAK and Fn14 is upregulated in many solid tumors compared with healthy tissues. The activation of TWEAK/Fn14 signaling enhances the proliferation, invasion, and migration of tumor cells. Moreover, the angiogenesis, pro-inflammatory cytokine expression, and epithelial–mesenchymal transitions are promoted upon TWEAK/Fn14 activation. Currently, the tumor necrosis factor receptor–associated factor and nuclear factor kappa B signaling pathways are considered two main downstream pathways activated by TWEAK/Fn14 interaction. In view of these facts, some TWEAK- or Fn14-targeting agents are generated to inhibit the progression of tumors and have achieved initial success in clinical and pre-clinical trials. These agents include monoclonal antibodies, fusion proteins, immunotoxins, and nanoparticles. In addition, some relevant signaling pathways are studied to identify new potential therapeutic targets. Overall, these findings suggest that the TWEAK/Fn14 pathway is critical in the development of tumors, and targeting this signaling is a potential therapeutic approach in future tumor therapy.